Juventud cubana ante la COVID-19: Estresores y estrategias de afrontamiento. / Cuban youth in the face of COVID-19: Stressors and coping strategies. - Claudia María Caballero Reyes; Arlety García Cabezas; Jorge Enrique Torralbas Oslé; Patricia Batista Sardain; Fany Gesto Mallo; Naomy López García; Ana Laura Escalona Díaz (Universidad de La Habana, 2021)
The epidemiological situation caused by Covid-19 has greatly impacted on the subjective dimension. Young people are among the groups most vulnerable to confinement and the situation generated by the pandemic in general. Constraints of the social structure, together with the socio-psychological characteristics of this age group, condition the main stressors that youth currently face (CEPAL, 2020). The objective is characterizing stressors and coping strategies in young people who accessed two groups from the WhatsApp Psychogroups psychological counseling service. Around 500 young Cubans participated. The content analysis of the 94 work sessions between two groups, Psycho-counseling Youth I and II, belonging to the remote psychological counseling service Psychogroups WhatsApp, was used. Four key areas of tension for young people are evident in the situation generated by the pandemic: personal, family, work / study and recreative. To cope with them, young people implement various strategies. There is a greater volume of strategies aimed at the area of tension directly related to the transmission of the disease; as well as a preponderance of active strategies oriented to the behavioral dimension, which show plurality and creativity in the elaboration of effective solutions. / RESUMEN La situación epidemiológica provocada por la COVID-19 ha impactado grandemente en la dimensión subjetiva. Los jóvenes se encuentran entre los grupos más vulnerables al confinamiento y a la situación generada por la pandemia en general. Constreñimientos de la estructura social, unidos a las características sociopsicológicas de este grupo etario, condicionan los principales estresores a los que se enfrenta la juventud actualmente (CEPAL, 2020). El objetivo de este artículo es caracterizar los estresores y las estrategias de afrontamiento en jóvenes que accedieron a dos grupos del servicio de orientación psicológica Psicogrupos WhatsApp. Participaron alrededor de 500 jóvenes cubanos. Se empleó el análisis de contenido de las 94 sesiones de trabajo entre dos grupos, Psico-orienta Jóvenes I y II, pertenecientes al servicio de orientación psicológica a distancia Psicogrupos WhatsApp. Se evidencian cuatro áreas fundamentales de tensión para los jóvenes ante la situación generada por la pandemia: personal, familiar, laboral/de estudio y recreativa. Para afrontarlas, los jóvenes implementan diversas estrategias. En conclusión, se aprecia un mayor volumen de estrategias encaminadas al área de tensión relacionada directamente con la transmisión de la enfermedad; así como una preponderancia de estrategias activas orientadas a la dimensión conductual, que muestran pluralidad y creatividad en la elaboración de soluciones efectivas.